ALZHEIMER'S DEMENTIA AND ORAL HEALTH OF ELDERLY - Dana-Gabriela Budală; Zinovia Surlari; Dragoș Ioan Virvescu; Carina Balcoș; Florinel Cosmin Bida; Monica Mihaela Scutariu; Elena Raluca Baciu (Romanian Dental Association for Education, 2021)
The improvement of the basic properties of dental restorative materials, such as their mechanical, physical, aesthetic, and bonding properties, has been dramatic and the current materials on the market show excellent clinical performance. This review article compiles the characteristics of ceramic dentures materials and the efforts made in order to improve the main features and to point out future perspectives.